When more is not better: A curvilinear relationship between foreign language proficiency and social categorization - Peltokorpi, Vesa; Pudelko, Markus (Journal of International Business Studies, 2021)
Expatriate host country language proficiency is predominately assumed to have a negative linear relationship with expatriate social categorization – as outgroup members – by host country national (HCN) employees in foreign subsidiaries. Departing from this assumption, we use social identity theory (SIT) and SIT-based sociolinguistics to hypothesize that expatriate host country language proficiency, due to identity threat, has a curvilinear U-shaped relationship with HCNs’ expatriate outgroup categorization: at first, outgroup categorization decreases with increasing expatriates’ language proficiency, but, from a certain point onwards, it increases because “too good” language proficiency violates salient intergroup boundaries between HCNs and expatriates. Due to their key roles in social categorization, we also examine whether HCN allocentrism and uncertainty avoidance moderate the proposed curvilinear relationship. Results from data collected from 1166 HCN employees in 956 foreign subsidiaries in Japan provide support for the main curvilinear relationship and the moderating curvilinear relationship of uncertainty avoidance. Our results suggest that the language-proficient expatriate social categorization relationship is more complex than previous international business research has evoked. Our study contributes to the international business literature by casting doubt on the widely held assumption that expatriate adaptation towards the host country always carries beneficial effects. Our study cautions, in particular, against the common assumption that higher proficiency in the host country language will automatically lead to better relationships with HCNs in foreign subsidiaries.